Effect of Plant Growth Regulators on Yield and Quality of Tomato (Solanum lycopersicum L.) under Mid-hill Conditions of Himachal Pradesh - Sharma, Deepa; Chauhan, Aanchal (International Journal of Bio-resource and Stress Management, 2019)
Tomato (Solanum lycopersicum L.) member of family solanaceae is the world’s most popular vegetable crop due to its wider adaptability to various agroclimatic conditions and multifarous uses. Plant growth regulators play an important role in increasing the growth, yield as well as quality of the produce if applied in suitable forms and at appropriate concentrations. Field experiments were conducted for two consecutive years during 2014 and 2015 to study the effect of plant growth regulators on tomato cultivar Solan Lalima. Six treatments of plant growth regulators viz. Vipul Booster (1 and 1.5 ml l-1), Triacontanol (1 and 1.5 ml l-1) and NAA (20 and 30 mg l-1 ) were applied to tomato plants 15 days after transplanting and were compared to untreated control. Observations on growth parameters, yield contributing traits and fruit quality as affected by PGR,s were recorded. All the hormonal treatments were found to enhance vegetative growth, yield attributes and fruit quality of tomato, especially Triacontanol. Application of triacontanol @ 1.5 ml l-1 (T4) recorded the maximum plant height (3.12 m), maximum number of leaves (39.5) , number of branches per plant (7.6), number of fruits per cluster (5.67) , number of fruits plant-1 (52.50), highest average fruit weight (72.2 g ) and fruit yield per plant (3.79 kg). Thus considering yield and other parameters, Triacontanol @1.5 ml l-1, 15 days after transplanting was found best to increase the yield in tomato as compared to other treatments under study.